Glass comprising crystalline phase
A glass with a crystalline phase, featuring high linear expansion coefficient and glass transition point, addresses the challenges of heat resistance and dimensional accuracy in high-temperature applications.
Patent Information
- Application Number
- JP2023181017
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
Existing glass substrates used in camera modules, semiconductor devices, and magnetic recording media face challenges in maintaining heat resistance and dimensional accuracy under high temperature conditions.
Development of a glass containing a crystalline phase, specifically comprising at least one of cristobalite, lithium disilicate, and petalite, with an average linear expansion coefficient of 85×10^-7/℃ or higher and a glass transition point of 680°C or higher.
The glass with a crystalline phase exhibits excellent heat resistance and maintains high dimensional accuracy even under high temperature conditions, reducing deflection and peeling, and enhancing mechanical strength and chemical durability.
Smart Images

Figure 2025070576000001 
Figure 2025070576000002
Abstract
Description
[Technical field]
[0001] The present invention relates to glasses that contain a crystalline phase. [Background technology]
[0002] The manufacturing methods of camera modules used in smartphones, various semiconductor elements, and magnetic recording media are becoming more sophisticated and complicated, and improvements in various performances are being demanded for the glass substrates used therein. For example, Patent Document 1 discloses a glass member that exhibits specific physical properties. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-347796 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a glass which is excellent in heat resistance and which is capable of maintaining high dimensional accuracy even under high temperature conditions. [Means for solving the problem]
[0005] The present invention provides the following: (Configuration 1) Contains at least one crystalline phase selected from the group consisting of cristobalite, lithium disilicate, and petalite; The average linear expansion coefficient at 100 to 300°C is 85 x 10 -7 / °C or more, The glass transition point is 680°C or higher. Glass containing crystalline phases. (Configuration 2) Contains SiO2, Al2O3, and Li2O, The average linear expansion coefficient at 100 to 300°C is 85 x 10 -7 / °C or more, The glass transition point is 680°C or higher. Glass containing crystalline phases. (Configuration 3) In terms of oxide, mass % SiO2 content: 65.0%~85.0% Al2O3 content: 1.5%~10.0% Li2O content: over 0% and up to 13.0% 3. A glass comprising the crystalline phase according to claim 1 or 2, (Configuration 4) In terms of oxide, mass % P2O5 content: over 0% and up to 5.0% ZrO2 content: 2.0% or more 4. A glass containing a crystalline phase according to any one of claims 1 to 3, wherein (Configuration 5) In terms of oxide, mass % B2O3 content: 0%~5.0% Na2O content: 0%~5.0% K2O content: 0%~5.0% MgO content: 0%~5.0% CaO content: 0%~5.0% ZnO content: 0%~5.0% TiO2 content: 0%~5.0% Gd2O3 content: 0%~5.0% Sb2O3 content: 0%~3.0% Nb2O5 content: 0%~3.0% 5. A glass containing a crystal phase according to any one of claims 1 to 4, wherein (Configuration 6) In terms of oxide, mass % 6. A glass containing a crystalline phase according to any one of claims 1 to 5, wherein [(SiO2 component content+Li2O component content) / Al2O3 component content] is 6.4 or more. (Configuration 7) 7. A glass containing a crystalline phase according to any one of claims 1 to 6, having a Vickers hardness of 700 or more. (Configuration 8) 8. A magnetic recording medium substrate, a semiconductor support substrate, or an optical substrate, which is made of a glass containing a crystalline phase according to any one of claims 1 to 7. Effect of the Invention
[0006] According to the present invention, it is possible to provide glass that has excellent heat resistance and is capable of maintaining high dimensional accuracy even under high temperature conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] Hereinafter, embodiments and examples of the glass containing a crystalline phase of the present invention will be described in detail. However, the present invention is not limited to the following embodiments and examples, and can be practiced with appropriate modifications within the scope of the object of the present invention.
[0008] [Glass containing crystalline phase 1] The glass containing a crystalline phase in the first embodiment of the present invention (hereinafter also referred to as "glass 1 containing a crystalline phase") contains at least one crystalline phase selected from the group consisting of cristobalite, lithium disilicate, and petalite, and has an average linear expansion coefficient of 85×10 at 100 to 300° C. -7 / °C or higher, and the glass transition point is 680°C or higher.
[0009] Since the glass 1 containing the crystalline phase has a high average linear expansion coefficient, when the glass is used as a substrate for a magnetic recording medium, a semiconductor support substrate, an optical substrate, etc., it is possible to reduce the difference in average linear expansion coefficient between the glass and adjacent metal parts, thereby improving dimensional accuracy and suppressing warping and peeling. In addition, since the glass has a high Tg, it is possible to suppress deformation during heating in the manufacturing process of various devices and deformation caused by use in high-temperature environments. The glass 1 containing a crystalline phase can be produced by appropriately adjusting the raw material composition and production conditions according to the production method and examples described below.
[0010] <Various physical properties> (Average linear expansion coefficient (α)) Glass 1, which contains a crystalline phase, has an average linear expansion coefficient of 85×10 at 100 to 300°C. -7 / ℃ or more, 87×10 -7 / ° C. or more. By having such a high average linear expansion coefficient, when used as the various substrates described above, it is possible to make the thermal expansion characteristics closer to those of surrounding metal parts, and thus improve the dimensional accuracy. The upper limit of the average linear expansion coefficient is not particularly limited, but may be, for example, 200×10 -7 / ℃ or less. The average linear expansion coefficient is measured by the method described in the Examples.
[0011] (Glass transition temperature (Tg)) The glass 1 containing a crystalline phase has a glass transition point of 680° C. or higher, and may be 690° C. or higher, 695° C. or higher, or 710° C. or higher. By having such a glass transition point, excellent heat resistance is exhibited. The upper limit of the glass transition point is not particularly limited, but is, for example, 900° C. or lower. The glass transition point is measured by the method described in the Examples.
[0012] (Vickers hardness (Hv)) The glass 1 containing a crystalline phase may have a Vickers hardness of 605 or more, 620 or more, 650 or more, or 700 or more. A high Vickers hardness has the advantage that the glass 1 containing a crystalline phase is less susceptible to scratches when used as the various substrates mentioned above. There is no particular upper limit to the Vickers hardness, but it is, for example, 1000 or less. The Vickers hardness is measured by the method described in the Examples.
[0013] (E / ρ) The glass 1 containing a crystalline phase may have a ratio E / ρ (stiffness per density) of Young's modulus E to specific gravity ρ of 35 or more, 35.5 or more, or 35.7 or more. A high E / ρ ratio means that the material is light and has high rigidity. For example, when the material is used as a substrate for a magnetic recording medium, deflection and vibration during high-speed rotation can be kept to a minimum. The upper limit of E / ρ is not particularly limited, but is, for example, 60 or less, or 50 or less. The Young's modulus of the glass 1 containing a crystalline phase may be, for example, 83 GPa or more, 85 GPa or more, or 87 GPa or more. There is no particular upper limit to the Young's modulus, but it is, for example, 120 GPa or less. The Young's modulus E and E / ρ are measured by the method described in the Examples.
[0014] <Glass containing crystalline phase> A glass containing a crystalline phase is a glass material having a crystalline phase and a glass phase, and is distinguished from an amorphous material. The crystalline phase of a glass containing a crystalline phase is identified using the angle of a peak that appears in an X-ray diffraction pattern of an X-ray diffraction analysis. The glass 1 containing a crystalline phase is, for example, crystallized glass, also known as glass ceramics, which is a material in which crystals are precipitated inside the glass by heat-treating the glass.
[0015] (crystalline phase) The crystalline phase-containing glass 1 contains at least one crystalline phase selected from the group consisting of cristobalite (eg, α-cristobalite), lithium disilicate, and petalite. In addition to the above, the glass 1 containing a crystalline phase may contain one or more other crystalline phases selected from the group consisting of lithium monosilicate, quartz, vergillite, and spodumene. The crystalline phase also includes a solid solution. The method for confirming the crystal phase is as described in the Examples.
[0016] In one embodiment, the crystalline phase-containing glass 1 includes, as crystalline phases, cristobalite and lithium disilicate. In one embodiment, the crystalline phase-containing glass 1 includes, as crystalline phases, cristobalite, lithium disilicate, and quartz. In one embodiment, the crystalline phase-containing glass 1 includes, as crystalline phases, cristobalite, lithium disilicate, lithium monosilicate, and petalite.
[0017] (Components) The components of the glass 1 containing a crystalline phase will be described. In this specification, the content of each component is expressed in mass% converted to oxide unless otherwise specified. Here, "oxide conversion" refers to the amount of oxide of each component contained in glass containing a crystalline phase expressed in mass% when the total mass of the oxide is taken as 100 mass% when it is assumed that all glass constituent components including a crystalline phase are decomposed and converted to oxide. In this specification, A% to B% means A% or more and B% or less.
[0018] In one embodiment, glass 1, which includes a crystalline phase, contains SiO2, Al2O3, and Li2O.
[0019] In one embodiment, glass 1 containing a crystalline phase contains the following components in the following composition in mass % calculated as oxide. SiO2 content: 65.0%~85.0% Al2O3 content: 1.5%~10.0% Li2O content: over 0% and up to 13.0%
[0020] In one embodiment, glass 1 containing a crystalline phase contains the following components in the following composition in mass % calculated as oxide. P2O5 content: over 0% and up to 5.0% ZrO2 content: 2.0% or more
[0021] The glass 1 containing a crystalline phase may have any one of the compositions described below, or may have a composition in which any of the compositions described below are appropriately combined. The SiO2 component is a framework component that constitutes glass containing a crystalline phase, and is a component that enhances stability and facilitates precipitation of a desired crystalline phase. When the content of the SiO2 component is 85.0% or less, it is easy to keep the viscosity low and the melting property is excellent, and when the content is 65.0% or more, the stability of the glass containing a crystalline phase can be improved. Therefore, the upper limit is preferably set to 85.0% or less, more preferably 83.0% or less, and even more preferably 80.0% or less. The lower limit is preferably set to 65.0% or more, more preferably 68.0% or more, and even more preferably more than 70.0%.
[0022] The Al2O3 component is a framework component that constitutes a glass containing a crystalline phase and enhances stability. When the content of the Al2O3 component is 10.0% or less, the transmittance is increased, and the glass has excellent resistance to devitrification and melting properties, while when the content is 1.5% or more, the glass has excellent stability. Therefore, the upper limit is preferably 10.0% or less, 8.0% or less, 5.9% or less, more preferably 5.5% or less, and even more preferably 5.3% or less. The lower limit is preferably 1.5% or more, more preferably 1.8% or more, and even more preferably 2.0% or more.
[0023] The Li2O component is a component for improving the meltability of the base glass, enhancing manufacturability, and facilitating the precipitation of a desired crystal phase. When the content of the Li2O component is 13.0% or less, the glass has excellent resistance to devitrification, and excellent heat resistance while maintaining good chemical durability. When the content of the Li2O component is more than 0%, the glass has a low viscosity, has excellent meltability, and can enhance manufacturability. Also, the desired crystal phase can be obtained. Therefore, the upper limit is preferably 13.0% or less, more preferably 12.0% or less, and can be, for example, 11.0% or less, 10.0% or less, or 9.5% or less. The lower limit is preferably 0.1 or more, 1 or more, 5.0% or more, more preferably 6.2% or more, and further preferably 7.0% or more, and can be, for example, 8.1% or more, or 9.0% or more.
[0024] The P2O5 component is a component for promoting the crystal formation of glass containing a crystalline phase. When the content of the P2O5 component is 5.0% or less, phase separation of the glass can be suppressed. When the content of the P2O5 component is more than 0%, the desired crystalline phase can be easily obtained. Therefore, the upper limit is preferably set to 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less. The lower limit is preferably set to more than 0%, more preferably 0.5% or more, and even more preferably 1.0% or more.
[0025] The ZrO2 component is a component that acts as a nucleating agent for crystals. When the content of the ZrO2 component is 12.5% or less, the melting property is excellent. When the content of the ZrO2 component is 2.0% or more, the transmittance is easily increased, and the precipitated crystals are excellent in uniformity and fineness, and the material has excellent mechanical strength and chemical durability. Therefore, the upper limit is preferably 12.5% or less, and can be, for example, 12.0% or less, 11.5% or less, 11.0% or less, 10.0% or less, or 9.0% or less. The lower limit is preferably 2.0% or more, more preferably 3.0% or more, and may be, for example, 4.0% or more, 5.0% or more, or 6.0% or more.
[0026] Although the glass containing the crystal phase according to the present invention can be produced even at 0% MgO, the glass improves low-temperature melting property when it is contained at more than 0%. When the content of the MgO component is 5.0% or less, the glass is easily strengthened when chemically strengthened. Therefore, the upper limit can be preferably set to 5.0% or less, more preferably 3.0% or less, and further preferably less than 2.0%. The lower limit can be preferably set to 0% or more, for example, 0.1% or more, or 0.2% or more. The content of the MgO component may be less than 2.5 mol %.
[0027] Although the ZnO component can produce glass containing the crystal phase according to the present invention even at 0%, it is a component that improves low-temperature melting property when contained at more than 0%. When the ZnO content is 5.0% or less, the glass is easily strengthened when chemically strengthened. Therefore, the upper limit can be preferably set to 5.0% or less, more preferably 3.0% or less, and even more preferably less than 2.0%. The lower limit can be preferably set to 0% or more, more preferably more than 0%, more preferably 0.1% or more, and even more preferably 0.2% or more.
[0028] Although the CaO component can produce a glass containing the crystalline phase according to the present invention even at 0%, it is an optional component that improves low-temperature melting property when contained at more than 0%. When the CaO content is 5.0% or less, the glass is easily strengthened when chemically strengthened. Therefore, the upper limit can be preferably set to 5.0% or less, more preferably 3.0% or less, and further preferably less than 1.0%. The lower limit can be preferably set to 0% or more, for example, more than 0%, 0.1% or more, 0.2% or more, or 0.3% or more. The content of the CaO component may be less than 5.0 mol %.
[0029] The K2O component and the Na2O component are components that improve the meltability of the raw glass and enhance manufacturability. When the content of each of the K2O component and the Na2O component is 5.0% or less, the glass has excellent resistance to devitrification, and excellent heat resistance while maintaining good chemical durability. In addition, even if the content of each of the K2O component and the Na2O component is 0%, the glass containing the crystal phase according to the present invention can be produced. However, when the content of each of the K2O component and the Na2O component exceeds 0%, the viscosity is easily kept low, the glass has excellent meltability, and the glass can be improved in manufacturability. Therefore, the upper limit of the Na2O component is preferably set to 5.0% or less, more preferably 4.0% or less, more preferably less than 3.0%, and even more preferably less than 2.0%. The lower limit is preferably set to 0% or more, more preferably 0.2% or more, and even more preferably 0.3% or more. The upper limit of the K2O component is preferably 5.0% or less, more preferably 4.0% or less, for example, 3.0% or less, 2.0% or less, or 1.0% or less. The lower limit is preferably 0% or more, more preferably 0.2% or more, even more preferably 0.3% or more, for example, 0.5% or more.
[0030] The Sb2O3 component functions as a fining agent when manufacturing raw glass. The upper limit is preferably 3.0% or less, more preferably 2.0% or less, more preferably 1.0% or less, more preferably 0.6% or less, and even more preferably 0.5% or less. The lower limit is preferably 0% or more, more preferably 0.01% or more, and more preferably 0.03% or more.
[0031] The B2O3 component is a component that has the effect of lowering the viscosity of the base glass. When the content of the B2O3 component is 5.0% or less, the glass has excellent resistance to devitrification and is easy to obtain the desired crystals. Although the glass according to the present invention can be produced even when the content of the B2O3 component is 0%, when the content exceeds 0%, the viscosity of the base glass is easily kept low and the melting property is excellent. Therefore, the upper limit can be preferably set to 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less. The lower limit can be preferably set to 0% or more, more preferably more than 0%, more preferably 0.1% or more, and even more preferably 0.3% or more.
[0032] The TiO2 component is a component that acts as a nucleating agent for crystals. When the content of the TiO2 component is 5.0% or less, the glass has excellent resistance to devitrification and excellent melting property of the raw glass. In addition, even if the content of the TiO2 component is 0%, the glass containing the crystal phase according to the present invention can be produced, but when the content of the TiO2 component is more than 0%, the desired crystal phase is easily obtained. Therefore, the upper limit is preferably 5.0% or less, more preferably 4.5% or less, and more preferably 4.0% or less. The lower limit is preferably 0% or more, for example, more than 0%, 0.1% or more, or 0.3% or more.
[0033] The Gd2O3 component is a component that improves hardness. When the content of the Gd2O3 component is 5.0% or less, the glass according to the present invention is excellent in resistance to devitrification. Although the glass according to the present invention can be produced even when the content of the Gd2O3 component is 0%, when the content exceeds 0%, the glass is excellent in improving hardness. Therefore, the upper limit can be preferably set to 5.0% or less, more preferably 4.5% or less, and more preferably 4.0% or less. The lower limit can be preferably set to 0% or more, more preferably more than 0%, more preferably 0.1% or more, and even more preferably 0.3% or more.
[0034] The Nb2O5 component is a component that improves hardness. When the content of the Nb2O5 component is 3.0% or less, the glass has excellent resistance to devitrification. In addition, even if the content of the Nb2O5 component is 0%, the glass according to the present invention can be produced, but when the content exceeds 0%, it is excellent in improving the hardness. Therefore, the upper limit can be preferably set to 3.0% or less, more preferably 2.0% or less, and more preferably 1.0% or less. The lower limit can be preferably set to 0% or more, more preferably more than 0%, more preferably 0.1% or more, and even more preferably 0.3% or more.
[0035] By setting the ratio of [(SiO2 component content + Li2O component content) / Al2O3 component content] to 6.4 or more, it becomes easier to generate α-cristobalite and lithium disilicate as crystal phases. Therefore, the upper limit of [(SiO2 component content + Li2O component content) / Al2O3 component content] is preferably 50.0 or less, more preferably 48.0 or less, and even more preferably 45.0 or less. The lower limit is preferably 6.4 or more, more preferably 13.9 or more, more preferably 14.5 or more, and even more preferably 15.0 or more.
[0036] The ratio [(K2O content + Al2O3 content) / ZrO2 content] may be set to 2.4 or less. By setting the ratio to 2.4 or less, it becomes easier to generate α-cristobalite and lithium disilicate as crystal phases. Therefore, the upper limit of [(K2O component content + Al2O3 component content) / ZrO2 component content] is preferably 2.4 or less, 1.5 or less, or less than 0.88, more preferably 0.87 or less, and even more preferably 0.85 or less. The lower limit is preferably 0.10 or more, more preferably 0.15 or more, and even more preferably 0.20 or more.
[0037] The ratio [(P2O5 content + K2O content + MgO content + Al2O3 content) / ZrO2 content] may be 5.2 or less. By setting the ratio to 5.2 or less, it is possible to easily generate α-cristobalite and lithium disilicate as the crystal phase. Therefore, the upper limit of [(P2O5 component content + K2O component content + MgO component content + Al2O3 component content) / ZrO2 component content] is preferably 5.2 or less, 4.0 or less, 2.0 or less, or less than 1.32, more preferably 1.28 or less, and even more preferably 1.25 or less. The lower limit is preferably 0.2 or more, more preferably 0.3 or more, and even more preferably 0.4 or more.
[0038] Although the glass according to the present invention can be produced even with 0% of the SrO component and the BaO component, they are optional components that improve low-temperature melting property when contained in excess of 0%. When the content of each of the SrO component and the BaO component is 5.0% or less, the glass is easily strengthened when chemically strengthened. Therefore, the upper limit of each of the SrO and BaO ingredients can be preferably set to 5.0% or less, more preferably 3.0% or less, and further preferably 1.0% or less.
[0039] When the total content of CaO and MgO components [CaO component content + MgO component content] is 5.0% or less, chemical strengthening becomes easy, and even at 0% the glass according to the present invention can be produced. However, when the content exceeds 0%, the glass has excellent melting properties. Therefore, the upper limit of [CaO component content + MgO component content] is preferably 5.0% or less, more preferably 3.0% or less, more preferably less than 3.0%, and further preferably 1.0% or less. Furthermore, a preferable lower limit of [CaO component content + MgO component content] can be 0% or more, for example, 0.1% or more, or 0.2% or more. The total content of the MgO component, the CaO component, the SrO component and the BaO component [the content of the MgO component + the content of the CaO component + the content of the SrO component + the content of the BaO component] may be less than 10.0 mol %.
[0040] Although the glass according to the present invention can be produced even if the total content of K2O and Na2O [K2O content + Na2O content] is 0%, when the content exceeds 0%, the viscosity is easily kept low and the melting temperature is kept low. In addition, when the content is 5.0% or less, the glass has excellent resistance to devitrification and excellent heat resistance while maintaining good chemical durability. Therefore, the upper limit of [K2O content + Na2O content] is preferably 5.0% or less, more preferably 4.0% or less, more preferably less than 4.0%, more preferably less than 3.0%, and even more preferably less than 2.0%. The lower limit is preferably 0% or more, more preferably 0.2% or more, and even more preferably 0.3% or more.
[0041] The ratio [Al2O3 component content / ZrO2 component content] may be more than 0 and not more than 1.0. By making it 1.0 or less, it becomes easier to obtain a desired crystal phase, and by making it more than 0, it becomes easier to stabilize the glass and the resistance to devitrification is excellent. Therefore, the upper limit of [Al2O3 component content / ZrO2 component content] is preferably 1.0 or less, more preferably 0.9 or less, and even more preferably 0.8 or less. The lower limit is preferably more than 0, more preferably 0.1 or more, and even more preferably 0.2 or more.
[0042] [Li2O component content + Al2O3 component content] may be 6.5% to 15.5%. By setting it to 15.5% or less, it becomes easier to suppress the formation of lithium aluminum silicate crystal phase, and by setting it to 6.5% or more, it becomes easier to obtain the desired crystal phase and to stabilize the glass. Therefore, the upper limit of [Li2O content + Al2O3 content] is preferably 15.5% or less, more preferably 15.0% or less, and may be, for example, 14.0% or less. The lower limit is preferably 6.5% or more, more preferably 8.0% or more, and even more preferably 10.0% or more.
[0043] The ratio [(Li2O component content + Al2O3 component content) / ZrO2 component content] may be 1.0 to 2.7. By setting it to 2.7 or less, it becomes easy to suppress the formation of lithium aluminum silicate crystal phase, and by setting it to 1.0 or more, it becomes easy to obtain a desired crystal phase and also to stabilize the glass. Therefore, the upper limit of [(Li2O component content + Al2O3 component content) / ZrO2 component content] is preferably 2.7 or less, more preferably 2.4 or less, and may be, for example, 2.1 or less. The lower limit is preferably 1.0 or more, more preferably 1.3 or more, and even more preferably 1.6 or more.
[0044] The ratio [SiO2 component content / (P2O5 component content+Li2O component content+Na2O component content+K2O component content)] may be 4.5 or more. By setting it to 4.5 or more, it becomes easier to obtain the desired crystal phase. Therefore, the lower limit is preferably 4.5 or more, and more preferably 5.0 or more. In addition, by setting [SiO2 component content / (P2O5 component content+Li2O component content+Na2O component content+K2O component content)] to 20.0 or less, it becomes easy to precipitate a desired crystal phase, and it becomes easy to keep the viscosity low, and the melting property is excellent. Therefore, the upper limit of [SiO2 component content / (P2O5 component content+Li2O component content+Na2O component content+K2O component content)] may be, for example, 20.0 or less, 10.0 or less, or 7.5 or less.
[0045] The ratio [K2O component content / ZrO2 component content] may be more than 0 and less than 0.5. By making it less than 0.5, it becomes easier to obtain the desired crystal phase, and by making it more than 0, it becomes easier to keep the viscosity low, the melting property is excellent, and it becomes easier to improve manufacturability. Therefore, the upper limit of [K2O component content / ZrO2 component content] is preferably less than 0.5, more preferably 0.4 or less, and further preferably 0.3 or less. The lower limit is preferably more than 0, for example, 0.1 or more.
[0046] The ratio [(K2O component content + Al2O3 component content) / ZrO2 component content] may be more than 0 and not more than 0.85. By making it 0.85 or less, it becomes easier to suppress the formation of lithium aluminum silicate crystal phase, and by making it more than 0, it becomes easier to stabilize the glass. Therefore, the upper limit of [(K2O component content + Al2O3 component content) / ZrO2 component content] is preferably 0.85 or less, more preferably 0.80 or less, and may be, for example, 0.75 or less. The lower limit is preferably more than 0, more preferably 0.1 or more, and even more preferably 0.2 or more.
[0047] The ratio [(K2O component content + Al2O3 component content) / (ZnO component content + ZrO2 component content)] may be more than 0 and not more than 0.95. By making it 0.95 or less, it becomes easier to suppress the formation of a lithium aluminum silicate crystal phase, and by making it more than 0, it becomes easier to stabilize the glass. Therefore, the upper limit of [(K2O component content + Al2O3 component content) / (ZnO component content + ZrO2 component content)] is preferably 0.95 or less, more preferably 0.90 or less, and even more preferably 0.85 or less. The lower limit is preferably more than 0, more preferably 0.1 or more, and even more preferably 0.2 or more.
[0048] The glass containing the crystalline phase of the present invention may or may not contain Bi2O3, Cr2O3, CuO, La2O3, MnO, MoO3, PbO, V2O5, WO3, and Y2O3 components, as long as the effect of the present invention is not impaired. Not containing these components has the effect of preventing the transmittance from deteriorating.
[0049] Furthermore, the glass containing a crystalline phase may or may not contain other components not mentioned above, as long as the properties of the glass containing a crystalline phase of the present invention are not impaired. For example, metal components such as Yb, Lu, Fe, Co, Ni, and Ag (including oxides of these metals) may be included.
[0050] Further, as a fining agent for glass, in addition to the Sb2O3 component, the glass may or may not contain one or more selected from the group consisting of SnO2 component, CeO2 component, As2O3 component, and F, NOx, and SOx. However, the upper limit of the content of the fining agent can be preferably set to 3.0% or less, more preferably 2.0% or less, more preferably 1.0% or less, and most preferably 0.6% or less.
[0051] On the other hand, since there has been a tendency in recent years to refrain from using Pb, Th, Tl, Os, Be, Cl and Se as harmful chemical substances, it is preferable that the material is substantially free of these components.
[0052] (Manufacturing method) Glass 1 containing a crystalline phase (e.g., crystallized glass) can be produced by uniformly mixing raw materials so that each component is within a specified content range, melt-molding the mixture to produce raw glass, and then crystallizing this raw glass.
[0053] The heat treatment for crystal precipitation may be a one-stage or two-stage heat treatment. In the two-stage heat treatment, a nucleation step is first performed by heat treatment at a first temperature, and after this nucleation step, a crystal growth step is performed by heat treatment at a second temperature higher than that of the nucleation step. The first temperature of the two-stage heat treatment can be preferably 400°C to 680°C, more preferably 450°C to 650°C, and further preferably 500°C to 600°C. The retention time at the first temperature is preferably 30 minutes to 2000 minutes, more preferably 180 minutes to 1440 minutes. The second temperature of the two-stage heat treatment is preferably 680° C. or higher, for example, 700° C. to 850° C., preferably 700° C. to 800° C., and more preferably 700° C. to 780° C. The holding time at the second temperature is preferably 30 minutes to 600 minutes, and more preferably 60 minutes to 400 minutes.
[0054] In one-stage heat treatment, the nucleation process and the crystal growth process are carried out consecutively at a single temperature. Usually, the temperature is raised to a predetermined heat treatment temperature, and after reaching the heat treatment temperature, the temperature is maintained for a certain period of time, and then the temperature is lowered. In the case of one-stage heat treatment, the heat treatment temperature is preferably 680° C. or higher, for example, 700° C. to 850° C., and preferably 700° C. to 800° C. The holding time at the heat treatment temperature is preferably 30 minutes to 500 minutes, and more preferably 60 minutes to 400 minutes.
[0055] (Strengthening method) The glass 1 containing a crystalline phase may be strengthened by various strengthening methods to form a compressive stress layer on the surface.
[0056] One method for strengthening glass containing a crystalline phase to form a compressive stress layer on the surface is, for example, a chemical strengthening method in which an alkali component present in the surface layer of the glass containing a crystalline phase is subjected to an exchange reaction with an alkali component having a larger ionic radius, thereby forming a compressive stress layer in the surface layer.
[0057] The chemical strengthening method can be carried out, for example, by the following steps: Glass containing a crystalline phase is brought into contact with or immersed in a molten salt of a salt containing potassium or sodium, such as potassium nitrate (KNO3), sodium nitrate (NaNO3), or a mixed salt or composite salt thereof. This treatment of bringing the glass into contact with or immersing the glass in the molten salt (chemical strengthening treatment) may be carried out in one step or two steps.
[0058] The method for strengthening the glass 1 containing a crystal phase is not limited to chemical strengthening, and for example, thermal strengthening or ion implantation may be used.
[0059] [Application] The glass 1 containing a crystalline phase can be used as a magnetic recording medium substrate, a semiconductor support substrate, or an optical substrate.
[0060] (Magnetic recording medium substrate) When used as a magnetic recording medium substrate, the magnetic recording medium is called a magnetic disk or a hard disk, and is used in internal storage devices of desktop personal computers, server computers, notebook personal computers, mobile personal computers, and the like. When glass 1 containing a crystalline phase is used as a substrate for a magnetic recording medium (e.g., a HAMR type magnetic recording medium), a magnetic recording layer containing a magnetic material is provided on the substrate to form the magnetic recording medium, and the magnetic recording device is made by including components such as a magnetic recording head. The magnetic recording layer and other components of the magnetic recording device may be of known type.
[0061] (optical board) Glass 1 containing a crystalline phase can be used as a substrate (optical substrate) for an optical module built into an optical device (imaging device) or the like, for example, as a substrate used in a camera module in which lenses and semiconductor sensors (CCD, CMOS, etc.) are stacked. One method for mass-producing such camera modules is wafer level optics technology, in which a large number of lens modules are formed on a single wafer and then cut, and glass 1 containing a crystalline phase can also be used in this method. In addition, glass 1 containing a crystalline phase can also be used as an optical filter substrate (optical substrate) for laminating optical filters, and can be utilized, for example, in the field of optical fiber communications, as a substrate for laminating dielectric filters for decomposing optical signals into wavelengths.
[0062] (Semiconductor Support Substrate) The glass 1 containing a crystalline phase can be used as a semiconductor support substrate for mounting various semiconductor elements. In this case, the glass 1 containing a crystalline phase may be used only during the production of the semiconductor element and not ultimately contained in the semiconductor element, or may be ultimately contained in the semiconductor element. As a method for manufacturing a semiconductor element, for example, there is a method (wafer level packaging technology) in which a semiconductor layer, a wiring layer, etc. are laminated on a glass substrate, and sealed with a sealing resin as necessary, and the glass substrate is peeled off by light irradiation or the like to obtain a semiconductor element, and the glass 1 containing a crystalline phase can also be used in this method.
[0063] [Glass containing crystalline phase 2] The glass containing a crystalline phase according to the second embodiment of the present invention (hereinafter also referred to as "glass 2 containing a crystalline phase") contains SiO2, Al2O3, and Li2O, and has an average linear expansion coefficient of 85×10 at 100 to 300° C. -7 / °C or higher, and the glass transition point is 680°C or higher. "Glass 2 containing a crystalline phase" differs from the above-mentioned "Glass 1 containing a crystalline phase" in that "Glass 2 containing a crystalline phase" does not necessarily have the requirement regarding the crystalline phase "containing at least one crystalline phase selected from the group consisting of cristobalite, lithium disilicate, and petalite," and in that "Glass 2 containing a crystalline phase" necessarily has the requirement regarding the composition "containing SiO2, Al2O3, and Li2O." However, in other respects it is the same as "Glass 1 containing a crystalline phase," and the matters explained for "Glass 1 containing a crystalline phase" can also be applied to "Glass 2 containing a crystalline phase."
[0064] Glass 2 containing a crystalline phase contains SiO2, Al2O3, and Li2O. The contents of these and other components are as explained in (Constituent components of glass) of "Glass 1 containing a crystalline phase" and can be applied to Glass 2 containing a crystalline phase.
[0065] In one embodiment, the glass 2 containing a crystalline phase contains at least one crystalline phase selected from the group consisting of cristobalite, lithium disilicate, and petalite. Details of the conditions and other characteristics of the crystalline phase are as explained in (Crystal Phase) of "Glass 1 containing a crystalline phase" and can be applied to the glass 2 containing a crystalline phase. EXAMPLES
[0066] Examples 1 to 8, Comparative Example 1 (1) Preparation of raw materials As the raw materials for each component of the glass containing a crystalline phase, the raw materials of the corresponding oxides, carbonates, or phosphates were selected, and these raw materials were weighed and uniformly mixed to obtain the compositions shown in Table 1. The composition of Comparative Example 1 is the same as that of Example 21 of Patent Document 1.
[0067] (2) Production of glass containing crystalline phases Next, the mixed raw materials were put into a platinum crucible and melted in an electric furnace at 1300°C to 1600°C for 2 to 24 hours depending on the degree of melting difficulty of the glass composition. The molten glass was then stirred to homogenize it, and the temperature was lowered to 1000°C to 1450°C, after which it was poured into a mold and slowly cooled to produce base glass. The obtained base glass was heated under the nucleation conditions and nucleus growth (crystallization) conditions shown in Table 2 to produce glass containing a crystalline phase. In addition, in Comparative Example 1, the original glass was not crystallized.
[0068] (3) Confirmation of crystal phase The crystalline phases contained in the glass containing the crystalline phase obtained in (2) were identified from the angles of the diffraction peaks appearing in the X-ray diffraction pattern measured using an X-ray diffraction analyzer (D8Discover, manufactured by Bruker). The confirmed crystalline phases are shown in Table 2. In the table, "Cri." is an abbreviation for α-cristobalite, "Li2Si2O5" is an abbreviation for lithium disilicate, "Li2SiO3" is an abbreviation for lithium monosilicate, "Quartz" is an abbreviation for quartz, and "Petalite" is an abbreviation for petalite.
[0069] (4) Young's modulus E The Young's modulus of the glass containing a crystalline phase obtained in (2) (comparative example 1 is the base glass) was measured by the ultrasonic pulse method of JIS R1602.
[0070] (5) Specific gravity ρ In accordance with the Japanese Industrial Standard JIS Z 8807 (2012) "Method of measurement of density and specific gravity of solids", the specific gravity of the glass containing the crystalline phase obtained in (2) (Comparative Example 1 is the original glass) was measured.
[0071] (6) Ratio of Young's modulus E to specific gravity ρ: E / ρ The ratio (E / ρ) was calculated by dividing the value of Young's modulus E obtained in (4) by the value of specific gravity ρ obtained in (5).
[0072] (7) Glass transition temperature Tg In accordance with the Japan Optical Glass Industry Association standard JOGIS08-2019 "Method for measuring thermal expansion of optical glass," the glass transition point (Tg) of the glass containing the crystalline phase obtained in (2) (Comparative Example 1 is the original glass) was measured.
[0073] (8) Average linear expansion coefficient α The average linear expansion coefficient was measured in the temperature range of 100°C to 300°C using a Bruker TD5000SA with reference to the Japan Optical Glass Industry Association standard JOGIS08-2019 "Method for measuring thermal expansion of optical glass." The glass containing the crystalline phase obtained in (2) (comparative example 1 is the original glass) was processed into a cylindrical shape with a diameter of 4 mm and a length of 20 mm, and the average linear expansion coefficient was calculated from the slope of the expansion curve showing the relationship between temperature and material elongation in the temperature range of 100°C to 300°C.
[0074] (9) Vickers hardness Hv A pyramidal indentation was made in the surface of the glass sample containing the crystalline phase obtained in (2) (the original glass in Comparative Example 1) using a diamond pyramidal indenter with a facing angle of 136°. The load was calculated based on the surface area (mm 2 The hardness was measured using a Shimadzu Corporation micro Vickers hardness tester HMV-G21D with a test load of 200 gf and a holding time of 10 seconds.
[0075] [Table 1]
[0076] [Table 2]
Claims
1. Contains at least one crystalline phase selected from the group consisting of cristobalite, lithium disilicate, and petalite; Average linear expansion coefficient at 100 to 300°C is 85 x 10 -7 / °C or more, The glass transition point is 680° C. or higher. Glass containing crystalline phases.
2. SiO 2 , Al 2 O 3 , and Li 2 Contains O, Average linear expansion coefficient at 100 to 300°C is 85 x 10 -7 / °C or more, The glass transition point is 680° C. or higher. Glass containing crystalline phases.
3. In terms of oxide, mass % SiO 2 Ingredient content: 65.0% to 85.0%, A 2 O 3 Ingredient content: 1.5% to 10.0%, Li 2 O content: over 0% and up to 13.0% 3. A glass comprising the crystalline phase according to claim 1 or 2,
4. In terms of oxide, mass % P 2 O 5 Content of ingredients: More than 0% and 5.0% or less ZrO 2 Ingredient content: 2.0% or more 3. A glass comprising the crystalline phase according to claim 1 or 2,
5. In terms of oxide, mass % B 2 O 3 Ingredient content: 0% to 5.0% Na 2 O content: 0% to 5.0% K 2 O content: 0% to 5.0% MgO content: 0% to 5.0% CaO content: 0% to 5.0% ZnO content: 0% to 5.0% TiO 2 Ingredient content: 0% to 5.0% G.D. 2 O 3 Ingredient content: 0% to 5.0% Sb 2 O 3 Ingredient content: 0% to 3.0%, Nb 2 O 5 Ingredient content: 0% to 3.0% 3. A glass comprising the crystalline phase according to claim 1 or 2,
6. In terms of oxide, mass % [(SiO 2 Content of component + Li 2 O content) / Al 2 O 3 3. The glass comprising the crystalline phase according to claim 1 or 2, wherein the content of each component is 6.4 or more.
7. 3. A glass comprising a crystalline phase according to claim 1 or 2, having a Vickers hardness of 700 or more.
8. A magnetic recording medium substrate, a semiconductor support substrate, or an optical substrate, which is made of the glass containing the crystalline phase according to claim 1 or 2.
Citation Information
Patent Citations
Glass member, product using the same, and method for production of the product
JP2006347796A